Employing the psycholinguistic programming (NLP) approach in preparing the interior designer (Journal of the College of Basic Education, 2022)
The process of preparing the designers process is not easy , especially when it comes to students of disciplines of the Design Arts in colleges and institutes of the Fundation of Technical Education for two reasons: The first reason that accepting these students accepted ˝ centrally ˝ and not special ˝ includes testing process that differentiation between students on the basis of possession of talent. The second reason for the existence of individual differences among them. This comes Search to run in this process by identifying problems impeding her and addressed by employing the researcher to approach (NLP) in the process of preparation as a curriculum interested in studying success and as a method stimulates the individual to discover the potentials unlimited and use it to make a personal change , particularly that employing this approach in various fields has given satisfactory results. This search consists of three chapters, the chapter one includes a simplification and the importance of search and it’s aim , also includes the limits and terms of the search. . chapter two includes two parts the first deals with ( NLP ) is defined by presenting the main principles ( hypotheses ), while the second part deals with the performing skill and factors affecting the acquisition. In the third chapter were identified research methodology and the research community and the sample research group measures taken by the researcher and down to achieve the goals search in the design of a practical method teaching depended on the principles of (NLP) is designed to guide the student and stimulated to achieve success in the acquisition of skill performance in a colors lesson , then apply the curriculum and test it to see the effectiveness of skill employed in giving to students. After designing and implementing practical approach new class of trainees covered that have been identified concluded researcher that the percentage of the progress of students who relied program in their applications higher than the progress of students who relied traditional way of four comparisons he made between the two groups , while the percentages equal in comparison Fifth, the Researcher believe this result is an indication of the validity of the program and thus the possibility of Utilization ( NLP ) to give students skills effectively. The researcher has concluded his recommendation and a list of Arabic and foreign scientific sources adopted.